Identification of Bacteriocin-Like Inhibitors from Rumen Streptococcus spp. and Isolation and Characterization of Bovicin 255 - Whitford, M. F. (American Society for Microbiology, 2001)
Streptococci obtained from rumen sources were tested for the production of antibacterial compounds using a deferred-antagonism plating assay. Of 35 isolates tested, 7 were identified that inhibited the growth of other streptococci. None of the inhibitory activity was due to bacteriophage. Three isolates, LRC0253, LRC0255, and LRC0476, were selected for further characterization. Analysis of 16S ribosomal DNA indicated that LRC0476 was a strain of Streptococcus bovis, while isolates LRC0253 and LRC0255 are likely strains of Streptococcus gallolyticus. The antibacterial compounds produced by these bacteria were protease sensitive, remained active in a pH range from 1 to 12, and did not lose activity after heating at 100°C for 15 min. The inhibitory peptide from strain LRC0255 was purified using pH-dependent adsorption and desorption to bacterial cells, followed by ammonium sulfate precipitation and reversed-phase chromatography and gel filtration. The peptide was 6 kDa, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. An oligonucleotide probe based on the N-terminal sequence of the purified peptide was used to identify the gene encoding the inhibitory peptide. The antibacterial peptide has characteristics that are very similar to those described for class II bacteriocins of gram-positive bacteria.